RFID tag antennas for IoT applications - Gwee, Kim Ming (Nanyang Technological University, 2023)
As the population of electrical vehicles (EV) in Singapore has significantly increased these few years, large number of EV chargers are required to install to provide the facility for EV drivers. Managing big stock of EV chargers with circular nozzle is a challenging task for the supplier. An UHF RFID tag antenna like patch antenna is usually constructed with a substrate and a ground plate. The ground plate material is copper, and the substrate material is FR4, both materials have a limitation of the flexibility to be attached on an object with a circular surface. However, PET substrate with high flexibility in physical shape is considered in the proposed tag antenna design. In this FYP, the objective is to design a low cost, flexible in shape and compact size UHF tag antenna with desirable performance in terms of return loss as well as read range. High compactness for the overall physical size of the proposed tag design has been achieved using a popular meander line technique. The tag antenna has been designed, simulated and analysed by using ANSYS HFSS student version software. Behaviour of the tag design in planar and in conformal was studied. Attaching the tag design to the cylindrical object made of polypropylene was analysed. Finally, the proposed tag antenna has been fabricated and S-parameters measurement was completed on the tag prototype by using 2-ports Vector Network Analyzer(VNA) with a test fixture. The read range of the tag prototype with a RFID microchip soldered on the antenna has been measured with a UHF RFID reader in the NTU Communication Research lab II located at S2-B3C-26.